2015
DOI: 10.1097/opx.0000000000000558
|View full text |Cite
|
Sign up to set email alerts
|

Different Amounts of Alcohol Consumption and Cataract

Abstract: Heavy alcohol consumption significantly increased the risk of age-related cataract, whereas moderate consumption may be protective for this ocular condition. Clinically, information on a patient's alcohol drinking history might be valuable to general physicians and ophthalmologists when there is a diagnosis of age-related cataract and should be collected on a routine basis in eye clinics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 35 publications
3
28
1
Order By: Relevance
“…Smoking is a well-established risk factor for cataract 29 . Heavy alcohol drinking was found to be associated with cataract in a recently published meta-analysis 30 . There is a need to identify the specific metabolic biomarkers which are linked with the growth of crystalline lens.…”
Section: Discussionmentioning
confidence: 95%
“…Smoking is a well-established risk factor for cataract 29 . Heavy alcohol drinking was found to be associated with cataract in a recently published meta-analysis 30 . There is a need to identify the specific metabolic biomarkers which are linked with the growth of crystalline lens.…”
Section: Discussionmentioning
confidence: 95%
“…However, it has been suggested, in contrast, that moderate alcohol consumption shows a beneficial influence on coronary heart disease, stroke, type 2 diabetes mellitus, and cataract (Rimm et al, 1999; Rehm et al, 2003; Koppes et al, 2005; Ronksley et al, 2011; Gong et al, 2015). Similarly, several epidemiological studies have also revealed that moderate alcohol consumption has a protective effect on the development of FLD (Dunn, Xu & Schwimmer, 2008; Gunji et al, 2009; Yamada et al, 2010; Hiramine et al, 2011; Dunn et al, 2012; Hamaguchi et al, 2012; Moriya et al, 2013; Sookoian, Castaño & Pirola, 2014; Hashimoto et al, 2015; Kächele et al, 2015; Moriya et al, 2015; Nishioji et al, 2015; Sogabe et al, 2015) It seems paradoxical because the excessive alcohol consumption causes alcoholic liver diseases (You & Crabb, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies also showed that important risk factors associated with cataract including income and educational level 28 , smoking 29 , diabetes 30 , sunlight exposure 31,32 , body mass index 33 , drug intake 33,34 , oestrogen replacement therapy 35 and alcohol 36 .…”
Section: Discussionmentioning
confidence: 98%